Advances in EU gender equality: missing the mark? - Renman, Vilde; Conroy, Caroline (Brussels, 2014)
"Gender balance has been a particularly salient issue in the recent process of formulating the list of designated commissioners. Jean-Claude Juncker’s success, as President-elect of the European Commission, in securing the designation of nine women as commissioners should be seen in perspective. Female representation in top EU positions remains low. This paper analyses the EP committees, finding a clear divergence in legislative influence between committees chaired by men and women. Although female political representation has been increasing, this is happening at a very slow pace and the most influential leadership roles in the EP remain dominated by men. This raises questions of the possible need to resort to stronger measures to improve female representation in the EU institutions."